2017
DOI: 10.1007/s10549-017-4134-7
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of aromatherapy versus conventional care for breast cancer patients during perioperative periods

Abstract: The results showed no effects of aromatherapy on QOL, sleep quality, and vital sign. However, there was not any harm or adverse event for using aromatherapy. All impressions from self-reporting were positive such as relaxed, comfortable, and enjoyable by the aromatherapy group. Therefore, we can use aromatherapy during perioperative periods in order to meet the expectations of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 17 publications
0
30
0
3
Order By: Relevance
“…e results showed no efficacy of aromatherapy in improving the quality of life, vital signs, and sleep quality. According to the Tamaki et al, insufficient sample size can be one of the reasons for finding no subtle changes in the quality of life, vital signs, and sleep quality of breast cancer patients [37]. Our results are not consistent with those of Tamaki et al, due to the use of different types of aromas and the short duration of intervention in the study by Tamaki et al In the present study, one type of aroma was used for each intervention group and the duration of the intervention was one week.…”
Section: Discussionmentioning
confidence: 99%
“…e results showed no efficacy of aromatherapy in improving the quality of life, vital signs, and sleep quality. According to the Tamaki et al, insufficient sample size can be one of the reasons for finding no subtle changes in the quality of life, vital signs, and sleep quality of breast cancer patients [37]. Our results are not consistent with those of Tamaki et al, due to the use of different types of aromas and the short duration of intervention in the study by Tamaki et al In the present study, one type of aroma was used for each intervention group and the duration of the intervention was one week.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their minimal cytotoxicity 13 , 14 , EOs are considered pharmaceutically safe and could represent a good alternative natural source of anticancer agents, thus deserving further investigations to ascertain their mechanism of action and to validate their possible clinical uses as alternative/complementary antitumor agents. In the last 20 years, preclinical studies demonstrated anticancer activity of either some EOs or their main components 15 , 16 and led to case–control studies 17 and clinical trials 18 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, while non-toxic, non-invasive and well received and tolerated, the inhaled Zingiber officinale EO was not an effective complementary therapy for chemotherapy-induced nausea and vomiting and health-related quality of life neither in children with cancer [258] nor in women with breast cancer [259]. While not showing any harm or adverse events, the study by Sasano's group evidenced no effects of aromatherapy on quality of life, sleep quality, and vital sign during perioperative periods of breast cancer patients [260]. Meta-analysis of three randomized controlled trials including a total of 278 participants did not show any clinical effect of aromatherapy massage on reducing pain in cancer patients [261].…”
Section: Clinical Use Of Eos For Cancer Patientsmentioning
confidence: 90%
“…Pharmacokinetic studies are needed to validate the safety and efficacy of EOs and their bioactive compounds. In fact, even if several papers indicated EOs and their components as safe and not toxic [258][259][260], hepatotoxicity described for monoterpenes and sesquiterpenes, major components of many EOs, should be also considered and should deserve more attention [264]. Further studies on terpene metabolism and toxicity need to be performed to avoid the risk of eventual liver injury.…”
Section: Discussionmentioning
confidence: 99%